Participatory Health Research Voices from Around the World (Springer International Publishing, 2018)
This groundbreaking resource explores core issues in participatory health research (PHR) and traces its global emergence as a force for improving health and well-being, health care services and quality of life. The PHR approach is defined as including community members, health practitioners and decision-makers as co-researchers, using local knowledge to reduce disparities in care, advocate for responsive health policy, and accelerate positive change in society as a whole. The book's first half surveys themes essential to the development of the field, including evaluating PHR projects, training professionals in conducting PHR, and the ambitious work of the International Collaboration for Participatory Health Research. International perspectives showcase the varied roles of PHR in addressing urgent local health problems in their specific public health and sociocultural contexts. Among the topics covered: Demonstrating impact in participatory health research Reviewing the effectiveness of participatory health research: challenges and possible solutions Kids in Action-participatory health research with children Participatory health research: an Indian perspective Participatory health research in Latin America: scientific production on chronic diseases Participatory health research in North America: from community engagement to evidence-informed practice Participatory Health Research benefits those teaching and learning about participatory health research at institutions of higher education and in community settings, addressing diverse fields including health promotion and disease prevention, medicine and public health, quality of life, social work and community development.